Influence of reactor hydrodynamics on sludge deposition and membrane performance in anaerobic membrane bioreactors - Liou, Cui Xian. (2013)
The inclusion of granular activated carbon (GAC) in membrane bioreactors (MBRs) can mitigate membrane fouling, partly due to their physical interaction with membrane surfaces. Fluid flow and membrane configuration affect sludge deposition onto membranes, the properties of the fouling layer, and subsequently substrate transport. The difficulty in understanding these phenomena is complicated by the multiphase nature and the unsteadiness of the flow. However, these factors can be studied using computational fluid dynamics (CFD) coupled with physical experiments. The objectives of this project were to utilize CFD to predict flow patterns in both anaerobic fluidized bed reactor (AFBR) and anaerobic membrane bioreactors (AFMBR). This allowed an assessment on how reactor configuration and membrane placement may affect sludge deposition. A multifluid Eulerian-Eulerian model with granular flow model was used to simulate the two phase flow in the lab scale reactor. The results obtained were compared with experimental results and good agreement between simulation and experimental observations on the fluidized bed flow profile and fluidized height was obtained. Proposed pilot-scale AFBR and AFMBR were simulated in a similar manner. AFBR simulation results showed that uniform fluidization was achievable and proved the effectiveness of using CFD to determine the optimal inlet velocity to achieve the required fluidization height. The simulation of AFMBR provided valuable information on the flow profile of GAC which was important in reactor design. Prediction of problems that might be encountered in the operation of the reactor was made possible. Examination of the velocity and volume fraction of the GAC on each membrane surface suggest that the fouling rate is nonhomogeneous and membrane element dependent. Elements nearer to the reactor center have little GAC in contact with the membrane surface but the GAC in this region has higher velocity which induce a high cross flow velocity. Membrane elements nearer to the reactor wall had more GAC in this region which will increase membrane performance with more GAC scouring. More GAC could be found outside the membrane module due to the lesser resistance pathway. The recirculation profile in the reactor was predicted which help in designing a better inlet structure that will be located evenly under the membrane module for better scouring effect. The simulation also highlighted the importance of reactor configuration and inlet design on the reactor hydrodynamics. With these simulation results, the optimal inlet design and inlet velocities were recommended.